A statistical study of fundamental toroidal mode standing Alfvén waves using THEMIS ion bulk velocity data. Issue 8 (25th August 2015) - Takahashi, Kazue; Hartinger, Michael D.; Angelopoulos, Vassilis; Glassmeier, Karl‐Heinz
Abstract We have studied the statistical properties of toroidal mode standing Alfvén waves with a fundamental eigenmode structure along the field line, denoted T1 waves, in the L range 7–12, using THEMIS‐D data for 2008–2013. T1 wave events were identified in hourly data segments using an automated procedure that detects narrowband oscillations in the azimuthal component of the ion bulk velocity. For each event we determined the frequency, amplitude, ellipticity, and the orientation angle of the polarization ellipse, and we examined the L and magnetic local time dependence of the detection rate and physical properties of the T1 waves. Confirming previous observations in space and on the ground, we found a pronounced dawn‐dusk asymmetry in the wave detection rate and amplitude. The detection rate in the dawn sector is approximately twice as high as that in the dusk sector, and the amplitude in the dawn sector is larger by ∼50%. The same asymmetry is also evident in the velocity amplitude averaged in the fixed Pc5 band (1.7–6.7 mHz) and in the amplitude of the electric field and field line displacement that are derived from the velocity amplitude. The ellipticity and the orientation angle of the polarization ellipse are organized by local time, in accordance with the theoretical prediction of toroidal mode waves excited by field line resonance with tailward propagating waves in the magnetosphere, which are in turn driven by external sources. Although infrequently, T1 waves are also detected in the midnight sector, suggesting magnetotail sources for this subset of events.